The effect of a targeted functional movement retraining intervention on anterior knee pain and associated biomechanical mechanisms - Leibbrandt, Dominique Claire (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.